Prevalence of maternal psychological disorders after immediate postpartum haemorrhage: a repeated cross-sectional study - the PSYCHE* study protoco - Marine Pranal; Anne Legrand; Ingrid de Chazeron; Pierre-Michel Llorca; Françoise Vendittelli (BMJ Open)
Introduction The main objective of this study is to assess the prevalence of depression at 2, 6 and 12 months postpartum in women who have had an immediate postpartum haemorrhage (PPH) (blood loss ≥500 mL within 24 hours of delivery). The secondary objectives are to assess the prevalence of anxiety and post-traumatic stress disorder among these women and to evaluate the prevalence of psychological disorders according to the severity of the PPH.Methods and analysis This repeated, cross-sectional, single-centre study will take place at the Clermont-Ferrand University Hospital (France). The population will comprise a cohort of women giving birth at a term ≥22 weeks of gestation.For each woman with a PPH (exposed), two women without PPH (unexposed) will be included: the women who give birth immediately before and immediately after her. The PPH will be managed according to French guidelines. The principal endpoint is the prevalence of depression, measured by the Edinburgh Postnatal Depression Scale (EPDS). The intervention will consist of four surveys including various self-completed questionnaires: the first during the immediate postpartum (Post-Delivery Perceived Stress Inventory (PDPSI), Spielberger'sState-Trait Anxiety Inventory (STAI)-Y-A and Y-B and Mini-International Neuropsychiatric Interview (M.I.N.I.) 5.0.0), then at 2 months (EPDS, STAI-Y-A, Generalised Anxiety Disorder (GAD-7) and Revised Impact of Event Scale (IES-R)), and finally at 6 months and 1 year postpartum (EPDS, STAI-Y-A, GAD-7, M.I.N.I. 5.0.0 and IES-R). The study will include 1542 women — 514 with PPH.Ethics and dissemination The institutional review board (IRB) approved the study on 14 February 2017 (IRB Sud Est VI: N°AU1243).Results will be reported in peer-reviewed journals and at scientific meetings. Findings from the study will be useful for individualising medical follow-up after childbirth, especially for woman who experienced a PPH, but also more generally in increasing birth professionals' awareness of effects of trauma. The evidence obtained might also lead to modifying practices and including this recommendation in French guidelines on PPH.Trial registration number NCT03120208.